Love online - Kaufmann, Jean-Claude.; Macey, David, 1949-2011. (Cambridge, UK : Polity, 2012)
The internet is changing the rules of the game of love. In a world where anything is possible, a potential date - whether it be a one-night stand or the start of a more lasting relationship - can be just a click away. Anyone looking for love online can throw off their inhibitions and can say what they have never dared to before. The internet revolution has ensured that online dating has now become both widespread and commonplace. Online users can buy into the consumerist illusion that they can choose a man or woman in the same way that they would shop for groceries - this is the new hypermarket of desire. Women in particular can enjoy a new sexual assertiveness. Where once they might have looked for an emotional attachment, they are now demanding simply the right to have a good time. However, love cannot be reduced to such simple terms. The apparently risk-free world of online dating is at odds with love in real life, which has its own demands and expectations. You cannot introduce another person into your life and expect everything to remain the same. Human beings have a way of turning your life upside down. -- Book Description.
Introduction -- Prologue : on the net -- pt. I. In real life.'You never know what to expect' -- First steps -- How to kiss -- A new dance -- pt. II. Pleasure and feelings. Should you have sex on a first date? -- Sex as leisure activity -- The game -- The'LoveSex' imbroglio -- pt. 3. Women, sex and love. Unbridled pleasure? -- The'bad boy' paradox -- Avoiding the traps -- Conclusion -- Appendix : On methodology.
Originally published in French as: Sex@mour. Paris : A. Colin, c2010.
Includes bibliographical references (p. [172]-176).
Keywords: Online dating; Dating (Social customs) -- Computer network resources; Man-woman relationships -- Computer network resources; Love -- Computer network resources; Sex; Internet; Liebe; Partnerwahl; 0; Zweierbeziehung